Peculiarities of proteome profile of eutopic endometrium in women with adenomyosis depending on fertility - O. M. Nosenko; O. M. Kosyuga (Journal of Education, Health and Sport, 2019)
In recent years, several studies have reported a correlation between adenomyosis and major obstetric adverse effects. Implantation failures can be caused by changes in the expression of some molecules, referred to as "implantation markers", which are expressed by the endometrium and are required for successful interaction between the embryo and endometrium. The purpose of the study was to determine the features of the proteomic profile of the endometrium in women with adenomyosis, depending on their fertility. Material and methods. A comparative immunohistochemical (IGC) analysis of 102 eutopic endometrial specimens from women of reproductive age with adenomyosis and infertility (group I) was performed; from 20 nonpregnant women with adenomyosis who had a history of desired pregnancy and ended in childbirth and did not record episodes of miscarriages (group II), as well as from 30 conditionally gynecologically healthy women who applied for the introduction of an intrauterine system for contraception (control group C). A biopsy of the eutopic endometrium was performed on P+6 day of the menstrual cycle, during the period of the expected implantation window, with the help of aspiration pipel-curette. In immunohistochemical (IGC) determination of the proteomic profile of the endometrium HOXA10 was stained with monoclonal antibodies (MAB) to HOXA10 (sc-17159, Santa Cruz Biotechnology, USA); LIF - murine MAB against LIF (J-14F: SC-80159, Santa Cruz Biotechnology Inc., USA); sgp130 - goat polyclonal antibodies (PAB) anti-gp130 (BAF 228, supplied 50 μg / ml, R&D Systems); IL-6 - primary rabbit antibodies (code No CXH1-066LS, supplied as rabbit IgG 20 µg / ml; Cambridge Bioscience, UK). Results. It was found that important factors of reproductive disorders in women with adenomyosis are: changes in the proteomic profile of the eutopic endometrium on the day of the expected implant window, such as a decrease in HOXA 10 expression in the stroma by 1.52 (p<0.01) and in the glands by 1.46 times (p<0.01), LIF in glands - in 1.12 (p<0.01) and sgp130 - in 2.52 (p<0.01), as well as increased secretion in glands of IL-6 in 1,99 (p<0.01) times. In fertile women with adenomyosis, less pronounced changes in the proteomic profile of the eutopic endometrium are observed, which creates the conditions for successful realization of reproductive intentions, including a decrease in expression of HOXA 10 in the stroma by 1.48 times (p<0.01), in the glands - in 1.12 (p>0.05); secretion in glands of LIF - in 1.06 (p>0.05) and gp130 - in 1.98 (p<0.01); increased IL-6 1.08 times (p<0.05). Conclusions. Changes in the proteomic profile of the endometrium play an important role in the occurrence of reproductive disorders in adenomyosis.